Groups with the same prime graph as the simple group Dn(5) - Babai, A.; Khosravi, B. (Український математичний журнал, 2014)
Let G be a finite group. The prime graph of G is denoted by Γ(G). Let G be a finite group such that Γ(G)=Γ(Dn(5)), where n≥6. In the paper, as the main result, we show that if n is odd, then G is recognizable by the prime graph and if n is even, then G is quasirecognizable by the prime graph.